Health information systems : design issues and analytic applications - McGlynn, Elizabeth A. (Directions in health services research and policy., 1998)
This book provides practical guidance on using information systems effectively to answer questions posed by a variety of stakeholders in the U.S. health care system, including consumers, purchasers, providers, and health system administrators. Providing an introduction to health services research techniques, the authors discuss the use of various data sources for analysis, as well as the integration of these data sources and the application of different analytic techniques to answering key policy questions. This book offers a broad overview of the critical issues in using information systems, as well as a technical section that addresses analytic topics of concern to researchers and analysts working in private and public sector groups responsible for purchasing, managing, delivering, and regulating health care services.